PENGARUH ASIMETRI INFORMASI, BOOK TAX DIFFERENCES, INVESTMENT OPPORTUNITY SET DAN STRUKTUR MODAL TERHADAP KUALITAS LABA - Zulanar Hasna; Muhammad Abdul Aris (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study basically aims to determine the effect of information asymmetry, book tax differences, investment opportunity set and capital structure on earnings quality. With a quantitative approach, the population in this study is an annual report on manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2018-2020. Secondary data in this study were collected from www.idx.com.id and the websites of each company. The sampling process in this study used a purposive sampling method and obtained 116 data as the final sample. The technique used in the data testing process in this study is a multiple linear regression analysis technique with SPSS version 25. The results of this study indicate that information asymmetry with a significant level of 10% and capital structure with a significant level of 5% has a significant effect on earnings quality. Meanwhile, book tax differences and investment opportunity set have no significant effect on earnings quality.